Avaliação clínica e molecular dos polimorfismos dos genes ECA 1 e ECA 2 na susceptibilidade à nefropatia diabética - Silva, Elisângela Gomes da (2018)
Diabetic nephropathy (DN) is one of the main causes of renal failure in diabetic patients. Studies indicate that the development and progression of nephropathy are strongly determined by genetic factors, and some have been shown to contribute to DN. The genetic insertion / deletion polymorphism of the angiotensin converting enzyme (ACE) gene is associated with an increase in the enzymatic activity of ACE, and several studies have already demonstrated the association of this polymorphism with ND. Another genetic polymorphism, G8790A of the gene converting enzyme angiotensin 2 (ACE 2), results in the alteration of the expression of this gene, however, it remains unknown until now the pathophysiological role of this G8790A polymorphism in type 1 and 2 diabetic nephropathy. The objective of this study was to establish a possible relationship between the genetic polymorphisms described and the development of diabetic nephropathy. A total of 101 patients with DN and 95 patients with diabetes mellitus (DM) were included in this hospital-based case-control study and the determination of the genotypes for the ACE gene polymorphism was done by real-time PCR (qPCR) and for the ACE 2 gene by PCR / RFLP, respectively. The ACE I / D genotype conferred an increased risk of developing DN (OR = 2.5 and p = 0.01), demonstrating that the D allele is responsible for the increase in circulating levels of angiotensin II (Ang II), leading to an increase of blood pressure, affecting the glomeruli and consequently causing glomerular damage. Regarding ACE 2, no association with the risk of DN was demonstrated. In patients with nephropathy, it was observed that the risk genotype (D / D) is associated with a tendency to increase glycated hemoglobin levels and decrease in systolic blood pressure levels. We conclude that the ACE gene polymorphism was relevant for the development of the clinical course of DN.